2019
DOI: 10.1111/jocn.15127
|View full text |Cite
|
Sign up to set email alerts
|

Mentors' self‐assessed competence in mentoring nursing students in clinical practice: A systematic review of quantitative studies

Abstract: Aims and objectives To examine registered nurses' self‐evaluation of their competence in mentoring nursing students in clinical practice. Background Clinical mentors have significant roles and responsibility for nursing students' clinical learning. Moreover, the mentors' role is becoming increasingly important internationally, as the role of nurse teachers in mentoring students in clinical practice has declined. However, in most EU countries there are no specific educational requirements for clinical mentors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 82 publications
3
31
0
10
Order By: Relevance
“…Nevertheless, sometimes this is jeopardized due to budget cuts or work overload (Wu et al., 2015). Additionally, nursing instructors need to undergo specific training that enhances their teaching competence, which most European countries presently lack (Pramila‐Savukoski et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, sometimes this is jeopardized due to budget cuts or work overload (Wu et al., 2015). Additionally, nursing instructors need to undergo specific training that enhances their teaching competence, which most European countries presently lack (Pramila‐Savukoski et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Nursing students' perception of the clinical work environment affects not only learning and acquisition of competence (Ramsbotham et al., 2019) but also recruitment and intention to stay (Lamont et al., 2015). In most European countries, a significant part of undergraduate education in nursing is carried out in a clinical context in hospitals (Pramila‐Savukoski et al., 2019). During their clinical placement, students are expected to gain clinical competencies such as independence, critical thinking, clinical judgment, problem solving skills, ethics, safety practices, and sense of responsibility as they progress (D’Souza et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We structured these preceptor outcomes based on findings from a recent study that identified a knowledge gap of preceptors' self-evaluated competence and a gap in preceptor confidence in determining the match between the rural preceptor and the APRN graduate student trainees they would precept during the rural traineeship. [26] The scoring of preceptor process and outcome measures is as follows: N/A -no opportunity, 1-Never Occurs, 2-rarely occurs 0%-39% of the time, 3-Occurs Sometimes 40%-69% of the time, 4-Usually Occurs 70%-89% of the time and 5-Occurs 90%-100% of the time.…”
Section: Methodsmentioning
confidence: 99%
“…Disse forholdene krever at sykepleieren som veileder har fagkunnskaper, pedagogiske ferdigheter og kommunikasjonsferdigheter (20). Sykepleierens veiledningskompetanse, motivasjon og engasjement er viktig for å understøtte studentenes laeringsprosesser (13,15,(20)(21)(22). Stillingenes omfang er 20 prosent ressurs, og de er organisert i klinikkvise team med en til to sykepleiere og en laerer i hvert team (3).…”
Section: Kombinerte Stillinger Styrker Kvaliteten På Laeringunclassified
“…Kombinerte stillinger trekkes frem som et viktig virkemiddel i arbeidet med å styrke kvaliteten på studentenes laering i praksisstudier (3,4,8,10). Kvaliteten på sykepleiernes veiledning har betydning for studentenes laering (11)(12)(13)(14)(15).…”
unclassified